Albumin Protein Adsorption on CoCrMo Implant Alloy: Impact on the Corrosion Behaviour at Localized Scale. Issue 3 (1st March 2022) - Rahimi, Ehsan; Offoiach, Ruben; Baert, Kitty; Terryn, Herman; Fedrizzi, Lorenzo; Lekka, Maria
Abstract : The protein adsorption and both its conformational arrangements and electrochemical interactions on the surface of metallic biomaterials has an immense impact on corrosion/biodegradation and biocompatibility of implantable metals. In this study, we used scanning Kelvin probe force microscopy (SKPFM) to reveal the synergistic effect of various bovine serum albumin (BSA) concentrations and overpotential conditions on BSA protein adsorption mechanisms and its influence on the corrosion behaviour of the CoCrMo alloy in phosphate-buffered saline solution. Electrochemical measurements showed that CoCrMo alloy was more resistant to corrosion in the 2 g l −1 BSA protein medium than in the 0.5 g l −1 one. The SKPFM analysis revealed a lower surface potential on the regions where BSA was adsorbed forming clusters, than on the un-covered CoCrMo substrate. When the surface overpotential and the protein concentration were increased from the OCP to +300 mV vs Ag/AgCl and from 0.5 to 2 g l −1, respectively, on both protein covering and surface potential were increased. Field emission scanning electron microscopy indicated that localized corrosion eventually occurred at the BSA protein/substrate interface owing to the adsorption of counterions and the difference between the surface potential values.